Peran Minuman Fungsional Berbasis Daun Ubi Jalar Pada Remaja Putri dengan Anemia di Lokus Stunting - Entin Jubaedah; Suratmi Suratmi; Moh. Hisyam Hermawan (Jurnal Ners, 2026)
Introduction: Functional drink is a functional food. As functional food, functional drinks must of course fulfill two main functions, namely providing nutritional intake and sensory satisfaction such as good taste and good texture. Sweet potato production in Indonesia from year to year has increased in 2014 production of 2,382,658 tons, slightly decreased in 2015 which amounted to 2,297,634 tons West Java Province is the largest sweet potato cultivator in Indonesia.. Sweet potato leaves can be used to increase the level of Fe will maintain the life of mice with anemia and increase Hb levels of pregnant women. Purpose: The aims of this research is to find out the effectiveness and role of sweet potato leaf-based functional drinks in adolescent girls with anemia as the first step in stunting prevention in Cirebon City Method: This study will use a Quasi Experiment design with a pretest-posttest control design approach. This design was chosen to measure the effectiveness of a functional drink intervention based on sweet potato leaves on increasing hemoglobin levels and nutritional status in adolescent girls with anemia at the stunting locus at the PONED Sitopeng Health Center Result: This functional drink formulation provides a contemporary taste and increases the content of vitamins and minerals. Fermentation of beverages also produces high levels of polyherorols, reaching 166 mg/L and 223 mg/L, Vitamin B6 as much as 0.07 mg, Vitamin C (3.7 mg), Magnesium (3.6 mg), Zinc (0.40 mg), Iron (0.92 mg) and Calcium (4.13 mg). Based on the results of the analysis, the comparison of the median Hb level of adolescent girls before the intervention was 11 and after the intervention was 14.8 and the p value was < 0.001, which means that statistically there is a significant difference between Hb before the intervention and after the intervention. Conclusion: Statistically, there was a median difference between Hemoglobin (Hb) levels before the intervention and after the intervention. The results of the study provide an idea that functional drinks made from sweet potato leaves are able to increase Hemoglobin (Hb) levels, so functional drinks based on sweet potato leaves are important to support the reduction of stunting.